THE POTENTIAL OF ARTIFICIAL INTELLIGENCE IN THE FIELD OF ECONOMICS OF GREEN ENVIRONMENTAL SUSTAINABILITY - Nadrljanski, Đorđe; Nadrljanski, Mila; Šimović, Vladimir (ACADEMIC REVIEW, 2023)
The modern development of science and technology is unthinkable without the use and development of almost all areas of artificial intelligence. Green environmental design includes project writing, site inspection, data collection, information arrangement and scheme selection, with the process of a constant search for answers. The continuous development of green environmental design is determined by the high-quality needs of human beings and modern society, and by highly technological, highly ecological, and systemically sustainable design concepts that are aligned with the development of time. The "Green Business" business strategy is based on profitability through environmentally friendly operational processes. A modern business with the help of artificial intelligence, its technologies, and techniques, and with “green thinking” can permeate the entire life cycle of production: products and plants, production lines and machines, products, and supply chains. The world today is struggling with the challenges of climate change and the need to reduce carbon dioxide emissions, and artificial intelligence has proven to be a powerful tool that can help optimize energy consumption, reduce harmful waste, and promote the use of renewable energy sources. The article examines the importance of the impact of artificial intelligence on green economic growth and all effective mechanisms by studying reference sources from the literature. Thanks to artificial intelligence, optimizing energy consumption in factories, buildings and cities is possible. Tools such as "predictive" maintenance and optimized consumption planning can reduce energy consumption, minimizing its harmful impact on the environment. With that, this paper aims to explore, clarify, and approximate a new development perspective, which includes artificial intelligence in its latest research, which focuses on the green industry.